Hybrid geometry / topology based mesh segmentation for reverse engineering. (June 2018) - Mejia, Daniel; Ruiz-Salguero, Oscar; Sánchez, Jairo R.; Posada, Jorge; Moreno, Aitor; Cadavid, Carlos A.
Highlights: We present an automatic geometry/topology segmentation algorithm. It requires far less parameters than state-of-the-art techniques. The algorithm produces fully parameterizable and functional partitions from scanned triangular meshes. It avoids over-segmentation by temperature-based merging the small sub-meshes. Graphical abstract: Abstract: Mesh segmentation and parameterization are crucial for Reverse Engineering (RE). Bijective parameterizations of the sub-meshes are a sine-qua-non test for segmentation. Current segmentation methods use either (1) topologic or (2) geometric criteria to partition the mesh. Reported topology-based segmentations produce large sub-meshes which reject parameterizations. Geometry-based segmentations are very sensitive to local variations in dihedral angle or curvatures, thus producing an exaggerated large number of small sub-meshes. Although small sub-meshes accept nearly isometric parameterizations, this significant granulation defeats the intent of synthesizing a usable Boundary Representation (compulsory for RE). In response to these limitations, this article presents an implementation of a hybrid geometry / topology segmentation algorithm for mechanical workpieces. This method locates heat transfer constraints (topological criterion) in low frequency neighborhoods of the mesh (geometric criterion) and solves for the resulting temperature distribution on the mesh. The mesh partition dictated by the temperature scalar map results in large, albeit parameterizable, sub-meshes. Our algorithm is tested with both benchmark repository and physical piece scans data. The experiments are successful, except for the well - known cases of topological cylinders, which require a user - introduced boundary along the cylinder generatrices.